(untitled) (FAVE Sección Ciencias Veterinarias, 2024)
The small strongyles are the most prevalent and important parasites in equines worldwide, and the widespread development of antihelmintic resistance is driving the application of selective treatments (ST) in young and adult equines to decrease or delay the development of these phenomena. This strategy is based on nematode egg counts per gram of feces (epg) from all members of the animal group to treat only those that exceed a certain threshold or cutoff point (CP) in egg count. In this context, the objective of this study was to report the results obtained in the application of ST for the control of equine strongyles on a farm in the province of Córdoba during a two-year period and to present an economic analysis comparing the cost of ST versus the usual practice of deworming all animals at fixed intervals. In both cases, a commercial paste formulation for equines containing moxidectin + oxfendazole + praziquantel was used. The results showed that only 20% of the equines required treatment each season of the year (CP=300 epg), which implied a large number of animals that did not have contact with anthelmintic drugs, a practice that favors parasite refuge.The results of two years of selective treatments (ST) application showed that only 20% of the equines required treatment in each season of the year (cut-off=300 epg), indicating a large number of animals that did not have contact with anthelmintic drugs, a practice that promotes parasite refuge. Additionally, it was observed that no equine needed more than two treatments per year, suggesting the possibility of reducing the sampling frequency for ST. However, it must be associated with an annual mass prophylactic treatment for the control of large strongyles and tapeworms. Economic analysis revealed that ST represented a 54% savings compared to mass deworming at fixed intervals, with anthelmintics being the highest costs among all analyzed. In conclusion, this study demonstrates the technical feasibility and economic advantages of ST for strongyle control in equines. These programs can prolong the lifespan of anthelmintics and reduce costs in the context of sustainable parasite control. However, the need for education and extension is emphasized for successful implementation of these programs as an essential step towards evidence-based veterinary medicine.